Niveles de Ventas en La Empresa la Cartilla del Cantón Ventanas - Ruiz Alcivar, Karla Estefania (2017)
The company La Cartilla, began its administration on October 29, 2009, located in the province of rivers, canton windows, street sucre and Velazco Ibarra (corner) which is characterized by the sale of clothing and household articles (in plastic materials) and utensils of kitchens etc., entering the market, being of great competition to the company Pica SA (branch), in the city of windows, province the rivers